STEPHANION. Homenaje a María Concepción Giner Soria, edición de Carmen Condoñer Merino, María Pilar Fernández Alvárez y José Antonio Fernández Delgado, Acta Salmanticensia (Estudios Filologicos), Salamanca, Ediciones Universidad de Salamanca, 1988, 254 pp (Minerva, 2019)
Review: STEPHANION. Homenaje a María Concepción Giner Soria, edición de Carmen Condoñer Merino, María Pilar Fernández Alvárez y José Antonio Fernández Delgado, Acta Salmanticensia (Estudios Filologicos), Salamanca, Ediciones Universidad de Salamanca, 1988, 254 pp.